POHON KEPUTUSAN DENGAN ALGORITMA C.45 UNTUK PENENTUAN TINGKAT RESIKO PENYAKIT GERD: Algoritma C45;Decision Support System;GERD;Web;Weka. - Puspitorini, Sukma; Wahyuning Astuti, Reny; Rivatunisa, Cyntia (LP2M Universitas Nurdin Hamzah, 2020)
Gastroesophageal Reflux Disease (GERD) is a disorder in which the contents of the stomach reflux repeatedly into the esophagus (esophagus), which causes symptoms and or complications that, interfere. The purpose of this study was to determine the level of risk of GERD in respondents based on diet, lifestyle, and perceived symptoms. The method used in this study is a decision tree with the C.45 algorithm. To make a decision tree WEKA tools are used, where data obtained from the results of a questionnaire distributed to 51 respondents to determine diet and lifestyle, then to predict the risk level of GERD a web-based decision support system was built using the Php programming language and the MySQL database. The input needs consist of respondent data input, questionnaire question data input, news data input, and training data input, with process requirements that include respondent data processing, questionnaire question data processing, news data processing, questionnaire data processing, and reporting process, which will produce training data output reports by gender, training data reports by date and prediction results. This study resulted in a design of a decision support system to determine the risk level of GERD that can help medical staff aware and educate the public to recognize early symptoms of GERD disease and to help general practitioners advise patients with GERD.